Interrogating the Historical and Cultural Context of Chinua Achebe’s Things Fall Apart - GBAGUIDI, CELESTIN; AHOSSOUGBE, Franck (My University, 2018)
This research paper focuses on the historical and cultural context of the publication of Things Fall Apart (1958) by Chinua Achebe. Before the release of this work by Achebe, the vast majority of literary writings on Africa and its inhabitants were produced by Western writers who offered a distorted view of the black continent and of its inhabitants. In response to this misrepresentation of Africa and Africans in colonial novels, Chinua Achebe and other African writers stood out as the voice of a self-centered narrative of Africa and its inhabitants, narrated from an African perspective. These committed African nationalist writers committed themselves to the deconstruction of the primal, ape image of Africa and Africans. This analysis aims to show that by presenting a false image of Africa, the colonial novels had the merit of making Africans aware of the need to write their own history, thus triggering the publication of Things Fall Apart and the other literary productions of the time that started the fight for real recognition of African culture and traditions in the rest of the world. In a critical postcolonial approach, the study positions an unsatisfied Chinua Achebe at the heart of the battle for the acknowledgement of Igbo / African culture and traditions. It interprets Things Fall Apart as an Afro-centric image offered to the European reader for a change of outlook on African culture and traditions.
Keywords: colonial novel - racism - biased description - Africa - rehabilitation novel